THE NIGHTMARE OF LITIGATING IN MULTIPLE FORA - Richter, Christopher (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 1999)
In his text Christopher Richter describes how Quebec courts determine their jurisdiction over commercial disputes. The author notes that while the rules and concepts found in the Civil Code of Quebec, the Code of Civil Procedure, international agreements, and Quebec jurisprudence appear at first glance to be straightforward, their application in combination often creates uncertainty. He explores concepts affecting jurisdiction, like connexity or domicile, and how the practical application of these concepts becomes difficult when the conflicting and evolving jurisprudence and legislation are considered. The author provides, however, more than a basic definitional analysis of the aspects influencing jurisdiction; he creatively posits how the conflicting rules, if manipulated carefully, can work flexibly to achieve a desired jurisdiction. To this end Christopher Richter considers several Quebec cases where the courts reached varying conclusions on the appropriateness of their jurisdiction based upon analyses of the alternating narrow and broad legislative rules (for example as between real and personal actions).